Characterization of odorous pollution and health risk assessment of volatile organic compound emissions in swine facilities. (15th February 2020) - Nie, Erqi; Zheng, Guodi; Ma, Chuang
Abstract: The odor pollution and health risk caused by intensive livestock buildings are a public concern. In this study, the concentration, odor pollution, and health risk from volatile organic compounds (VOCs) released from different locations on a swine farm (swine nursery house, fattening swine house, manure storage, plant boundary and upwind locations) in different seasons (spring, summer, and fall) were evaluated quantitatively. The average VOC concentrations were 125.5, 1504.7, and 1698.5 μg/m 3 in spring, summer, and winter, respectively. The total odor activity value ( OAV SUM ) of manure storage was the highest, with methanethiol, dimethyl sulfide (DMS), and H2 S as the major contributors. Cumulative noncarcinogenic emissions exceeded the threshold in summer at all locations, except at the plant boundary and upwind locations. Furthermore, the cumulative carcinogenic risk threshold was also exceeded at the fattening swine house and manure storage area during the summer. Therefore, to protect farm staff working near the animal housing facilities, special attention should be paid to minimize the odorous nuisance and noncarcinogenic and carcinogenic risks. Graphical abstract: Image 1 Highlights: The VOCs released from different locations on a swine farm were measured over a year. Odor pollution results revealed that methanethiol is the dominant sulfuric compound. The non-carcinogenic and carcinogenic risks posed by VOCs were quantified. Health risk to VOC exposure is within an acceptable limit, except for manure storage.